Association between abdominal hernia and the risk of subsequent dementia - Hung, Kuo‐Chuan (Brain Behav, 2019)
OBJECTIVE: Matrix metalloproteinases (MMPs) may play a role in the pathophysiology of neurodegenerative disease and hernia formation. This retrospective cohort study was designed to assess whether there is an association between hernia and the risk of dementia. MATERIALS AND METHODS: Patients (≥45 years) with hernias were identified between 2000 and 2008 from a longitudinal claims data of one million beneficiaries from Taiwan's National Health Insurance program. A control group of patients with comparable distributions of sex, age, socioeconomic status, urbanization, and medical comorbidities without hernia were chosen for matching in a ratio of 1:1. Patients previously diagnosed with dementia were excluded. Follow‐up ended on December 31, 2013. Incidence rate of dementia was compared between patients with hernias and those without. Cox proportional hazards models were used to estimate hazards relative to those of the control group. RESULTS: After matching, there were 4,784 hernia and 4,784 nonhernia patients. Hernia patients showed a higher incidence rate and hazard ratio of dementia than those in nonhernia group (8.82 vs. 7.19/1,000 person‐years; adjusted hazard ratio [aHR], 1.24; 95% CI, 1.07 to 1.45; p < .01). Advanced age (p < .0001), hypertension (p = .0139), head injury (p = .0003), and stroke (p = .041) were found to be risk factors for dementia, while patients with high socioeconomic status (p < .01) and history of coronary artery disease (p = .0292) were unlikely to develop dementia in our cohort study. CONCLUSION: Patients with hernias were associated with a higher incidence of dementia than those without. Our finding should be validated in further prospective studies with larger samples.